Rekrutierungen für die Waffen-SS in Südosteuropa : Ideen, Ideale und Realitäten einer Vielvölkerarmee - Zaugg, Franziska 1977- (De Gruyter, 2021)
What advantages do people hope for when they collaborate with an occupying regime? What kinds of threats do they face if they do not? These questions can be applied to Waffen-SS recruitment during World War II and refracted as if through a prism. This study explains the intentions and scope of action of the occupational forces, political elites, and individuals in six states